THE ACTIVITY OF COUNCILS IN THE TURKIC KHAGANATE: THEIR ROLE IN THE POLITICAL GOVERNANCE SYSTEM (Western European Journal of Historical Events and Social Science, 2026)
This article provides a comprehensive analysis of the council (kurultai) as an important institution within the political governance system of the Turkic Khaganate. The study examines the composition of the council, its functions, decision-making mechanisms, and its role in state administration based on historical sources. Additionally, the research highlights how the council facilitated the participation of tribal elites in political processes and contributed to the legitimization of the khagan’s authority. The findings indicate that the council served as a key institution in strengthening central authority and ensuring political stability in the Turkic Khaganate.